2007
DOI: 10.1055/s-2007-965998
|View full text |Cite
|
Sign up to set email alerts
|

Photocycloaddition of 2,3-Dihydro-2,2-dimethyl-4H-thiopyran-4-one (a 4-Thiacyclohex-2-enone) to bona fide Triplet Quenchers. A Contradiction?

Abstract: 2,3-Dihydro-2,2-dimethyl-4H-thiopyran-4-one undergoes regiospecific photocycloaddition to 2-chloroacrylonitrile as well as regio-and stereospecific photocycloaddition to ethylidenemalononitrile. On irradiation in the presence of either 2,3-dimethylbuta-1,3-diene or isoprene, the same enone affords mainly [2+2]-cycloadducts and only minor amounts of (stepwise) [2+4]-cycloadducts, whereas quantitative quenching is observed in the presence of 2,5-dimethylhexa-2,4-diene. In contrast, the corresponding pyran is alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In this context, we have recently observed that the three six-membered ring enones 1a -1c also differ in their rigidity due to the differences in CÀS, CÀC and CÀO bond lengths, respectively [9]. Indeed, the more flexible dihydrothiopyranone 1b (d(CÀS) % 1.81 ) on excitation undergoes addition to conjugated alkenes efficiently, whereas the more rigid 1a and 1c react inefficiently due to competitive energy transfer [10]. We have now used this effect by changing (longer) CÀC (% 1.54 ) by (shorter) CÀO (% 1.43 ) bonds in seven-membered cyclic enones.…”
mentioning
confidence: 99%
“…In this context, we have recently observed that the three six-membered ring enones 1a -1c also differ in their rigidity due to the differences in CÀS, CÀC and CÀO bond lengths, respectively [9]. Indeed, the more flexible dihydrothiopyranone 1b (d(CÀS) % 1.81 ) on excitation undergoes addition to conjugated alkenes efficiently, whereas the more rigid 1a and 1c react inefficiently due to competitive energy transfer [10]. We have now used this effect by changing (longer) CÀC (% 1.54 ) by (shorter) CÀO (% 1.43 ) bonds in seven-membered cyclic enones.…”
mentioning
confidence: 99%
“…Similarly, 2 behaved like (the parent) benzocyclohept-5-en-7-one [5] by affording a roughly 1 : 1 mixture of head-to-head dimers with the two above mentioned configurations. In its reaction with 2,3dimethylbuta-1,3-diene, (monocyclic) enone 1 behaved very similarly to 2,3-dihydro-6,6-dimethylthiin-4-one (19) [11] by affording both [2 þ 2] and [2 þ 4] photocycloadducts via biradicals 20 and 21, respectively. Again, the higher flexibility of 1 as compared to that of thiacyclohexenone 19 is the reason for the relatively higher overall ratio of trans-fused bicycles from 20 (56%) as compared to those from 21 (10%).…”
mentioning
confidence: 99%
“…Nevertheless, it has been observed that irradiation of cyclohex-2-enone itself in neat buta-1,3-diene resulted in the formation of a mixture of [2 þ 2]-cycloadducts [4]. Subsequently, it has been shown that cyclic enones with lower E T values, e.g., 2,3-dihydro-2,2-dimethyl-4H-thiopyran-4-one [5], 3-(alk-1-ynyl)cyclohept-2-enones [6], and even acyclic 4-acylbut-1-en-3-ynes [7] undergo efficient [2 þ 2]-photocycloadditions to 1,3-dienes under standard enone þ alkene reaction conditions, i.e., by using a slight excess of alkene. Very recently, the [2 þ 2]-photocycloaddition of 5-phenylfuran-3(2H)-ones to cyclohexa-1,3-dienes has been successfully applied as key step in the total synthesis of biyouyanagin A and its analogs [8].…”
mentioning
confidence: 99%